The timing of Mediterranean sapropel deposition relative to insolation, sea-level and African monsoon changes. (15th May 2016) - Grant, K.M.; Grimm, R.; Mikolajewicz, U.; Marino, G.; Ziegler, M.; Rohling, E.J.
Abstract: The Mediterranean basin is sensitive to global sea-level changes and African monsoon variability on orbital timescales. Both of these processes are thought to be important to the deposition of organic-rich sediment layers or 'sapropels' throughout the eastern Mediterranean, yet their relative influences remain ambiguous. A related issue is that an assumed 3-kyr lag between boreal insolation maxima and sapropel mid-points remains to be tested. Here we present new geochemical and ice-volume-corrected planktonic foraminiferal stable isotope records for sapropels S1 (Holocene), S3, S4, and S5 (Marine Isotope Stage 5) in core LC21 from the southern Aegean Sea. The records have a radiometrically constrained chronology that has already been synchronised with the Red Sea relative sea-level record, and this allows detailed examination of the timing of sapropel deposition relative to insolation, sea-level, and African monsoon changes. We find that sapropel onset was near-synchronous with monsoon run-off into the eastern Mediterranean, but that insolation–sapropel/monsoon phasings were not systematic through the last glacial cycle. These latter phasings instead appear to relate to sea-level changes. We propose that persistent meltwater discharges into the North Atlantic (e.g., at glacial terminations) modified the timing of sapropel deposition by delaying the timing of peak African monsoon run-off. These observations may reconcile apparent model–data offsets with respect to the orbital pacing of the African monsoon. Our observations also imply that the previous assumption of a systematic 3-kyr lag between insolation maxima and sapropel midpoints may lead to overestimated insolation–sapropel phasings. Finally, we surmise that both sea-level rise and monsoon run-off contributed to surface-water buoyancy changes at times of sapropel deposition, and their relative influences differed per sapropel case, depending on their magnitudes. Sea-level rise was clearly important for sapropel S1, whereas monsoon forcing was more important for sapropels S3, S4, and S5. Highlights: Chronological framework for sapropels S1–S5, African monsoon, and sea-level change. Insolation–monsoon/sapropel phasings not systematic over the last glacial cycle. Meltwater release at glacial terminations delays monsoon and sapropel onset. Sea-level rise and monsoon run-off both important for sapropel formation.